Pre- and postoperative expression of circulating CEACAM1 and CEACAM6 using a nanoparticle-supported, lectin-specific assay detected in serum from patients with colorectal cancer - Kanani, Arezo; Alexeeva, Marina; Vinod, Rufus; Pettersson, Kim; Leivo, Janne; Søreide, Kjetil (Taylor & Francis, 2026)
Background
Biomarkers for colorectal cancer (CRC) measured in blood at various time-points represents potential tools for disease monitoring and additional staging complementing tissue-based diagnostics. Currently, the only marker in routine clinical use is carcinoembryonic antigen (CEA). Other carcinoembryonic antigen-related cell adhesion molecules (CEACAM) such as CEACAM1 and CEACAM6, have been implicated in tumour progression, however their serum levels in relation to clinical features remain insufficiently explored.
Materials and methods
Serum levels of CEACAM1 and CEACAM6 glycovariants were analysed by a novel nanoparticle-supported detection method in patients undergoing curative-intent surgery for CRC (stage I–III) in a prospective biomarker study (ACROBATICC; NCT01762813), comparing pre- and postoperative levels alongside conventional CEA detection for comparison. Correlations of pre- and postoperative levels of glycovariants with clinicopathological variables and recurrence were assessed.
Results
Serum levels were measured in 120 patients, of which 95 patients had CRC stage I–III. We observed a significant decrease in serum levels of CEA, CEACAM1, and CEACAM6 in serum from pre-surgery to post-operative measurement (p < 0.001), likely reflecting tumour burden reduction after surgery. No significant correlations between CEACAM1 or CEACAM6 were observed, nor any association to recurrence nor survival. However, expression of CEACAM6 postoperatively was correlated with liver metastasis compared to metastasis in other locations.
Discussion
Serum CEACAM6 from early and locally advanced CRC may reflect tumour biology in CRC but require validation in larger cohorts to determine prognostic value, utility as a serum-based biomarker for disease monitoring or, for prediction of recurrence risk.